Feasibility of Implementing Opioid Stewardship Recommendations for Sinonasal Surgery. (3rd November 2020) - Jordan, Jaxon W.; Spankovich, Christopher; Stringer, Scott P.
Abstract : Objective: The objective of our study was to review the current literature pertaining to perioperative opioids in sinus surgery and to determine the effects of implementing opioid stewardship recommendations in the setting of endoscopic sinonasal surgery. Study Design: Single‐institution retrospective case‐control study. Setting: Academic medical center outpatient area. Methods: This retrospective review comprised 163 patients who underwent routine functional endoscopic sinus surgery, septoplasty, and/or inferior turbinate reduction before and after implementation of a standardized pain control regimen based on published opioid stewardship recommendations. The regimen consisted of an oral dose of gabapentin (400 mg) and acetaminophen (1000 mg) at least 30 minutes prior to surgery, absorbable nasal packing soaked in 0.5% tetracaine intraoperatively, and a postoperative regimen of acetaminophen and nonsteroidal anti‐inflammatory medications. Tramadol tablets (50 mg) were prescribed postoperatively for breakthrough pain. The primary outcome measure for the study was the average number of hydrocodone equivalents (5 mg) prescribed before and after the new protocol. Results: The average number of opioid medications prescribed, measured as hydrocodone equivalents (5 mg), decreased from 24.59 preprotocol to 18.08 after the initiation of the new perioperative regimen ( P <. 001). There was no significant difference between the periods ( P >. 05) in number of postoperative phone calls regarding pain or in patient satisfaction scores. Conclusion: Opioid stewardship recommendations can be instituted for sinonasal surgery, including multimodal perioperative pain management and substitution of tramadol for breakthrough pain, as a method to decrease the volume of opioids prescribed, without increasing patient phone calls or affecting the likelihood of physician recommendation Press Ganey scores.